Perkembangan Sistem Pendidikan di Korea Selatan dan Perbandingannya dengan Sistem Pendidikan di Indonesia - Intan Maharani; Fatya Ayuni; Mislaini Mislaini (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The education system in each country has differences from each other, just like the education system in Indonesia and South Korea. The two have differences that can be compared so that the South Korean education system can be a reference for the Indonesian education system because considering that South Korea is a country that highly upholds education. In this case, the most noticeable difference between the two is in the level of literacy, educational facilities, and learning time. To reduce the level of disparity, developments and changes can be made, especially in the education system in Indonesia. This can start from equity in education so that all people have the same right to learn at school.